Influenza vaccination in health-care workers: an evaluation of an on-site vaccination strategy to increase vaccination uptake in HCWs of a South Italy Hospital - Luigi Vimercati; Francesco Paolo Bianchi; Francesca Mansi; Beatrice Ranieri; Pasquale Stefanizzi; Sara De Nitto; Silvio Tafuri (Taylor & Francis Group, 2019)
Despite the international recommendation and specific programs, and although the vaccination of health-care workers (HCWs) is considered the main measure to prevent nosocomial influenza, vaccination coverage (VC) among HCWs remains low. One of the most important barriers to vaccination uptake is the time required to attend a vaccination clinic. Centers for Disease Control and Prevention (CDC) recommends on-site influenza vaccination as a proven and cost-effective strategy that increases productivity, reduces overall absenteeism and prevents direct health-care costs. In order to increase vaccine compliance in the HCWs, the Hygiene and the Occupational Medicine departments of Bari Policlinico General University-Hospital, in the 2017/18 influenza season, promoted an on-site vaccination program in eight Operative Units (OUs). We investigated the influenza VC among HCWs of Bari Policlinico (n = 3,397), comparing VC after implementation of the on-site strategy by the Hygiene department during the 2017/18 influenza season to VC in 2016/17 season. For 2017/18 season, we also compared VC in OUs target of on-site strategy with data from in eight "control" Units (choose by simple random sampling) not included in the on-site offer. In the 2016/17 influenza season, 295/3,397 HCWs were vaccinated (VC: 8.7%) while in the 2017/18 season 482 HCWs (VC: 14.2%) received the vaccination. In OUs target of on-site vaccination, 71 HCWs (VC: 10.0%) were vaccinated in the 2016/17 season and 126 (18.0%) in the 2017/18 season, of which 101/126 (80.2%) were vaccinated in an on-site clinic. VC in OUs target of on-site vaccination increased between 2016/17 and 2017/18 seasons of 16.8 ± 10.4% (range: 5.5-37.1), while the coverage in OUs of the control group increased of 1.6 ± 2.2% (range: −1.7-4.5), with a significant difference (p < .05). Our study suggests that the offer of on-site vaccination during the 2017/18 season led to an increase of VC in HCWs compared to the classical vaccination clinic approach. The determinants of adhesion and not-adhesion must be analyzed in dept, to experiment, in the future, new good clinical practices to increase the vaccination coverage in HCWs.